Aplikasi Rekam Medis Elektronik Ibu Hamil - Tominanto Tominanto; Tria Puspita Sari (Politeknik Indonusa Surakarta, 2019)
The authority and obligations of midwife practices in Indonesia are regulated in the Decree of the Minister of Health of the Republic of Indonesia No.900 / Menkes / SK / VII / 2002 concerning Registration and Practice of Midwives. Delivery assistance allowed by midwives are normal and emergency deliveries, and basic health services only deal with minor cases that are within their capabilities. Implementation of midwife practice services found many problems regarding the management of medical records of pregnant women that have not been optimal, including: incomplete medical records, difficulties in searching for medical record data, less synchronous data, recording and reporting of basic health services that are often too late. This can result in a decrease in the quality of health services for pregnant mother patients until delivery. An alternative solution to this problem is to develop an electronic medical record application for pregnant women that can present a complete and accurate history of the examination and development of the health of pregnant women so as to improve the health services of pregnant women and facilitate the reporting process to related parties. The method of developing an electronic medical record application for pregnant women uses the waterfall method with stages of development: system requirements analysis, system design, implementation and system testing. The programming language used by PHP and MySQL databases. This application program consists of 1) data input for pregnant women, 2) input for examining pregnant women, 3) input medical treatment, and 4) report on examination results. The test results show that this application can store and present information about the health history of pregnant women with a valid so that it can be used as an alternative service for medical records of pregnant women that is more optimal.